The Impact of Prior Trial Experience on Mock Jurors’ Note Taking During Trials and Recall of Trial Evidence - Lorek, Joanna; Centifanti, Luna C. M.; Lyons, Minna; Thorley, Craig (Frontiers in Psychology, 2019)
Although jurors’ recall of trial evidence is often incomplete and inaccurate, courts rely on jurors’ ability to remember trial evidence to reach just verdicts. Note taking has been found to enhance jurors’ memory of trial evidence. However, the impact of serving on multiple trials on juror note taking and recall has not been examined. Findings from the educational literature demonstrate that students who are more experienced at note taking will take more notes and recall more lecture material. Thus, the current study is the first to investigate if similar benefits are obtained in jurors. Sixty participants attended two experimental sessions and acted as mock jurors. In each session, they watched one of two trial videos, a criminal and a civil trial (order of trials was counterbalanced). All jurors were permitted to take notes whilst watching the trials. Lastly, they were asked to reach a verdict and recall as much trial evidence as they could remember (none of the jurors had access to their notes during the recall task). Jurors wrote down more correct and critical evidence during the second session when compared to the first session. However, there was no statistically significant difference between session one and session two with regards to the quantity of correct and critical evidence jurors recalled. Thus, the present study demonstrates that trial experience enhances mock jurors’ note taking, however, there is no additional enhancement regarding recall.